Determinan Penggunaan Konstrasepsi (Analisis Hasil SDKI Tahun 2017 Provinsi Jawa Tengah) - urip tri wijayanti (Inovasi, 2020)
The purpose of this study was to obtain determinants of contraceptive use in women of childbearing age in Central Java Province. This research is a quantitative study with a cross sectional study design (cross section). The data used in the latest 2017 IDHS raw data in Central Java province include the number of live children (MV201), wife's age (MV013), husband's education (SM 108), wife's education (MV 106), wife's employment status (MV 717), place staying (MV 025), wealth index (MV 190), access to KB information sources via radio (MV 384 A), access to KB information sources via television (MV 384 B), access to KB information sources through magazines (MV 384 C), use contraception (MV 313). Data processing was performed using the SPSS 22 program. After that it was analyzed, including the characteristics of each research variable with the frequency distribution displayed in the percentage of each data group. Next bivariate analysis to see the relationship between independent variables with the dependent variable using Chi Square. The result is that there are several variables that are determinants of contraceptive use / have a relationship in contraceptive use, these variables include the number of children born, wife's education, wife's occupation, residence, getting family planning information through television media and reading family planning information in magazines using contraception. While the variables that have no relationship with contraceptive use include the wife's age, husband's education, wealth index, listening to family planning information from the radio with contraceptive use. His recommendation is to disseminate information on family planning programs thoroughly in interesting and inviting language, especially on radio media. socialization is also not limited to women, so that men increasingly understand family planning programs and participate in decision making Keywords: Determinant, Use of Contraception, Fertile Age Women